O capital no campo e suas novas articulações no município de Terra Rica - PR - Toniol, Fernanda Perdigão da Fonseca (2017)
The various phases through which it crossed the Northwest region of Paraná and, consequently, the city of Terra Rica, and how it influenced its agrarian economic base, also reveal the various forms of articulation of the capital in the countryside in these spaces. Since the time of its colonization, where the coffee culture was the flagship of the economy, the capitalist relations in the field were already recognized, but at different levels of what is later to be replaced by crops (pastures) and currently with the Sugarcane and other temporary crops. The research sought to apprehend the new articulations engendered by the capital in the countryside in the city of Terra Rica, as well as the new configurations resulting from this process supporting as central hypothesis the idea that the intensification of the capital in the field in the last decades has generated a process of reconfiguration in Its agricultural space, reflecting consequently in the geographic space, especially after the installation of a sugaralcohol plant. The main objective was to investigate both the articulations engendered by the capital in the field and the new configurations in the local space resulting from this insertion and intensification of the activity of the capital in the field, emphasizing the specificities of this phenomenon and its nature and still revealing Its diversity, movement and evolution as spatial organization. Having as support a qualitative methodological contribution, we used research techniques such as fieldwork and observation, allied to other techniques such as open and semi-structured interviews and the case study. From the analysis of data, information, readings and observations in the studied area, it was understood that, in the current context, the articulations of capital in the countryside present greater intensity, speed and dynamism, redefining roles (rural and urban) and reconfiguring relationships of various spheres (social, economic and labor). In addition, rural leases, the concentration of land and capital, the exploitation of the rural worker, typically capitalist relationships permeated by relations considered non-capitalist, revealed a reality peculiar to the area of study. The complex movement of this reality, which generates the new articulations, is not only due to the influence of local factors, but to the global movement which in turn presents a (contradictory) logic and follows an order within this (combined) universe, that is, does not act randomly. In this context, it was understood that the game established by capital includes in its plot, both the hegemonic agents and those who are at the margin of the system, in order to guarantee their reproduction.